Short-term and medium-term survival of critically ill patients with solid tumours admitted to the intensive care unit: a retrospective analysis. Issue 10 (18th October 2016) - Fisher, Richard; Dangoisse, Carole; Crichton, Siobhan; Whiteley, Craig; Camporota, Luigi; Beale, Richard; Ostermann, Marlies
Abstract : Objectives: Patients with cancer frequently require unplanned admission to the intensive care unit (ICU). Our objectives were to assess hospital and 180-day mortality in patients with a non-haematological malignancy and unplanned ICU admission and to identify which factors present on admission were the best predictors of mortality. Design: Retrospective review of all patients with a diagnosis of solid tumours following unplanned admission to the ICU between 1 August 2008 and 31 July 2012. Setting: Single centre tertiary care hospital in London (UK). Participants: 300 adult patients with non-haematological solid tumours requiring unplanned admission to the ICU. Interventions: None. Primary and secondary outcomes: Hospital and 180-day survival. Results: 300 patients were admitted to the ICU (median age 66.5 years; 61.7% men). Survival to hospital discharge and 180 days were 69% and 47.8%, respectively. Greater number of failed organ systems on admission was associated with significantly worse hospital survival (p<0.001) but not with 180-day survival (p=0.24). In multivariate analysis, predictors of hospital mortality were the presence of metastases (OR 1.97, 95% CI 1.08 to 3.59), Acute Physiology and Chronic Health Evaluation II (APACHE II) Score (OR 1.07, 95% CI 1.01 to 1.13) and a Glasgow Coma Scale Score <7 on admission to ICU (OR 5.21, 95% CI 1.65 to 16.43). Predictors of worse 180-day survival were the presence of metastases (OR 2.82, 95% CI 1.57 to 5.06), APACHE II Score (OR 1.07, 95% CI 1.01 to 1.13) and sepsis (OR 1.92, 95% CI 1.09 to 3.38). Conclusions: Short-term and medium-term survival in patients with solid tumours admitted to ICU is better than previously reported, suggesting that the presence of cancer alone should not be a barrier to ICU admission.